1998
DOI: 10.1136/jnnp.65.5.791
|View full text |Cite
|
Sign up to set email alerts
|

Headache characteristics in subarachnoid haemorrhage and benign thunderclap headache

Abstract: One third of patients with aneurysmal subarachnoid haemorrhage (ASAH) present with headache only. A prompt diagnosis is crucial, but these patients must be distinguished from patients with non-haemorrhagic benign thunderclap headache (BTH). The headache characteristics and associated features at onset in subarachnoid haemorrhage and benign thunderclap headache were studied to delineate the range of early features in these conditions. In this prospective study, one of two observers interviewed 102 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
1
13

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(142 citation statements)
references
References 12 publications
9
119
1
13
Order By: Relevance
“…The headache is instantaneous and reaches its peak rapidly (seconds to minutes). 1 Meningism, nausea and vomiting are common but not invariable. Seizures and loss of consciousness may occur at onset.…”
Section: Intracranial Haemorrhagementioning
confidence: 99%
“…The headache is instantaneous and reaches its peak rapidly (seconds to minutes). 1 Meningism, nausea and vomiting are common but not invariable. Seizures and loss of consciousness may occur at onset.…”
Section: Intracranial Haemorrhagementioning
confidence: 99%
“…43 TCH represents one of the most recurring symptom of neurological disease in the ED. 44 The first etiology to be searched in case of a suddenonset headache is properly represented by the subarachnoid hemorrhage (ESA). 45 In fact many systematic reviews and observational studies have demonstrated that about 70% of ESA is characterized by a thunderclap pattern.…”
Section: Thunderclap Headachementioning
confidence: 99%
“…It is generally abrupt in onset and reaches maximal intensity instantly. However, this classic description is seen in only 50% of patients presenting with aneurysmal SAH [8]. Conversely, in those patients prospectively screened for acute severe headache, only 6-17% were demonstrated to have SAH [9,10].…”
Section: Clinical Presentationmentioning
confidence: 99%